4CPS-192 Analysis of adherence and associated risk factors in multiple sclerosis patients under disease-modifying therapy. Issue 1 (23rd March 2023) - Sopena, L; Magallon, A; Frutos, A; Garcés, M; Iñiguez, C; Fresquet, R; Gomez, P; Vinuesa, JM; Merchan, A; Salvador, T; María Ángeles, AB
Abstract : Background and Importance: Multiple sclerosis (MS) is one of the most frequent causes of disability among young people. Understanding patients' adherence to treatments is of great importance to assess the effectiveness and safety of the prescribed treatments. Aim and Objectives: To analyse the adherence of patients with MS that were prescribed with disease-modifying treatment (DMT) and to identify risk factors. Material and Methods: A retrospective observational study was conducted including MS outpatients under active DMT in 2021. Variables collected: gender, age, drug type (subcutaneous interferon beta 1b, intramuscular interferon beta 1a, subcutaneous interferon beta 1a, teriflunomide, dimethyl fumarate, fingolimod), route of administration (oral vs parenteral), polypharmacy (> 5 drugs/day), adverse effects (AEs), type of MS (relapsing remitting MS -RRMS-, secondary progressive MS -SPMS-, primary progressive MS -PPMS-), time course, Expanded Disability Status Scale (EDSS) score at onset of DMT, number of previous flares and hospitalisations, and comorbidities. Adherence was calculated through the Medication Possession Ratio (MPR) using pharmacy dispensation record database. Good adherence was considered MPR ≥ 80%. A statistical analysis was performed with IBM SPSS Statistics v21.0. Results: A total of 214 patients were included [(62.1% female), mean age 43.9 (SD 9.7) years]. The most prescribed drug was teriflunomide (26.6%), followed by dimethyl fumarate (20.6%), subcutaneous interferon beta 1b (14.5%), glatiramer acetate (12.6%), fingolimod (12.1%), intramuscular interferon beta 1a (7.0%), and subcutaneous interferon beta 1a (6.5%). The most frequent route of administration was oral (59.3%) vs parenteral (40.7%). 38.3% of patients were polymedicated and 53.7% suffered AEs. 95.3% of patients had RRMS and 4.7% had SPMS. Median time with MS was 11 (0.2 – 45) years and median EDSS was 1.5 (0 – 8). Previous flare-ups were 51.4%, hospitalisations 39.3% and comorbidities 79.4%. Good adherence (MPR≥ 80) was determined for 89.7% of the patients. Median MPR was 100 (19 – 100). Adherence was influenced by route of administration (p=0.024) and comorbidities (p=0.014) with statistically significant differences. A statistically significant difference was not observed for the any other variable. Conclusion and Relevance: Adherence was satisfactory in most patients. Determining modifying factors of adherence is important to identify patients at risk of non-adherence who shall receive personalised pharmaceutical care and optimised treatment. References and/or Acknowledgements: Conflict of Interest: No conflict of interest